CAMPUR KODE DAN FUNGSINYA DALAM KOMUNITAS PEMAIN MOBILE LEGEND BANG BANG: KAJIAN ETNO SOSIOPRAGMATIK - martua reynhat sitanggang; kaleb simanungkalit (Universitas Negeri Medan, 2021)
The aimed of this research is todescribe the code writing & the function in the community of Mobile Legend Bang Bang players and the specific terms which is used of that community,especially found at Pasar baru, Sibuntuon Parpea Villages Lintongnihuta subdistrict. An ethno sociopragmatic approach used to analyze the data Which related to code writing, function of code writing & special terms which used of the community Mobile Legend Palayer in the Subdistrict mentimed. Collecting the data Conducted with technique of observation & interview. Result of the reseach found about 43 special terms that used of Batak Toba language Speaker. Phenomenon of that code writing happened about the factor of limitation by using code of the speaker Which is as the users of BBT so that if it is used Batak Toba Language because less of efficient. This Phenomenon Finally affected their Comunnication in the real life. So,the function of code writing in this phenomenon is to optimize and to effective the used of Vocabularies in Batak Toba Language.